Leveraging Innovation Resources for Modular Products under Open Innovation Scenarios Using Fuzzy Distance Method - Hai-jun Wang; Chao-hui Shu (Discrete Dynamics in Nature and Society)
In an open innovation environment, it is meaningful for manufacturing enterprises targeting global markets to integrate qualified innovation resources. In this paper, the linkage between product modularity and open innovation is first discussed, revealing a role that modular product architecture plays in linking enterprises’ innovation requirements and innovation resources as external innovation inputs. Next, indices for evaluating external innovation resources are developed. An evaluation method based on fuzzy distance is then proposed, which is intended to select optimal resources for the core modules of modular product architecture. A modular product of Haier Group is used as a typical case to verify the proposed method. Consistent evaluation results of innovation resources are achieved for different decision-making attitudes. Another finding regarding the case enterprise is that the resource management mechanisms it employs lead to a win-win cooperative relationship with its partners.